STRATEGI KOMUNIKASI KRISIS SEBAGAI UPAYA RESILIENSI EKONOMI PARA PETERNAK BABI PASCA SERANGAN VIRUS ASF - Astraguna, I Wayan; Kartika, Komang Reza; Cahyani, Ni Kadek Gita (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
The ASF (African Swine Fever) virus outbreak resulted in a 100% mortality rate among the pig population in Tomoni Timur District. This situation has severely impacted the local economy, with a significant portion of the community losing their sources of income. The government has implemented crisis communication strategies as an effort to enhance the economic resilience of the local community. This research aims to explore effective crisis communication strategies for bolstering the economic resilience of pig farming communities following an ASF virus outbreak. The study adopts a qualitative approach with a case study design. Data sources include observations, interviews, documentation, and literature review, with data analysis stages comprising data collection, data presentation, and conclusions. The findings of this research reveal that economic resilience efforts within the community can be facilitated through the implementation of crisis communication strategies, including Crisis Communication Plan Development, Proactive and Transparent Communication, and Reconstruction of Trust and Livestock Subsector Resilience. Furthermore, the community's response to crisis communication strategies involves increased awareness levels, active public engagement in government decisions, and impacts on economic resilience.